N-Heterocyclic olefins and thioureas as an efficient cooperative catalyst system for ring-opening polymerization of δ-valerolactone. Issue 14 (12th March 2019) - Zhou, Li; Xu, Guangqiang; Mahmood, Qaiser; Lv, Chengdong; Wang, Xiaowu; Sun, Xitong; Guo, Kai; Wang, Qinggang
Abstract : An organocatalytic ring-opening polymerization of δ-valerolactone has been developed. Abstract : An organocatalytic ring-opening polymerization of δ-valerolactone has been developed. The cooperative combination of N-heterocyclic olefins (NHOs) and thioureas (TUs) serves as an efficient catalyst for the synthesis of poly(δ-valerolactones) (PVLs), delivering products in high yields and selectivities. Nine different cooperative combinations of NHOs and TUs have been applied for the ROP of δ-valerolactone. In the screening of the NHO1/TU1 catalytic system, the catalyst ratios, monomer concentration and solvent effects were investigated in detail. The NHO1/TU1 catalyst system with a NHO/TU/BnOH/δ-VL ratio of 1 : 2 : 2 : 100 displayed the highest reactivity with 97% yield in 4 h at room temperature. The average number of molecular weight falls in the range of 6.0–7.0 kg mol −1 and molecular weight distribution is in the range of 1.1–1.2. The 1 H NMR and MALDI-TOF MS measurements of the resulting PVLs clearly indicated the linear polymer chain capped with BnO, indicating that the NHO/TU cocatalyzed ROP of lactones proceeded through a bifunctional mechanism. Furthermore, this strategy disclosed a new application of N-heterocyclic olefins in combination with the thiourea cocatalyst for the facile synthesis of polyesters.